Development of the Healthy Work Collaborative: Findings From an Action Research Study to Inform a Policy, Systems, and Environmental Change Capacity-Building Initiative Addressing Precarious Employment. Issue 1 (January 2021) - Welter, Christina; Jarpe-Ratner, Elizabeth; Bonney, Tessa; C. Pinsker, Eve; Fisher, Elizabeth; Yankelev, Anna; Kapadia, Devangna; Love, Marsha; Zanoni, Joseph
Precarious employment (PE) is a complex problem that affects an increasing number of workers across all economic sectors who experience low wages, hazardous conditions, and few benefits, and results in adverse health outcomes. PE is characterized by nontraditional work arrangements, precluding workplace-based interventions. Policy, systems, and environmental initiatives that engage cross-sectoral stakeholders may be an applicable health promotion approach to address PE. The University of of Illinois at Chicago Center for Healthy Work's Healthy Communities through Healthy Work (HCHW) is an outreach project of the Centers for Disease Control and Prevention/National Institute for Occupational Safety and Health–funded Center of Excellence for Total Worker Health that conducted a multiphased qualitative action research (AR) study. AR designs may be a novel approach to develop initiatives to address problems like PE. This article reports on HCHW's first AR phase to answer four research questions: (1) What are participants' perceptions of PE? (2) What are participants' perceptions of their roles in addressing PE? (3) What initiatives are under way that address PE? and (4) How can the findings be used to facilitate opportunities for healthy work? Key informant interviews with health (public health and health care; N = 23) and labor sector organizations (worker centers, worker advocacy organizations, and unions; N = 21) were conducted. Data were thematically analyzed alongside a chart-based content analysis, and shared in 11 key stakeholder meetings. Findings revealed an opportunity for the labor sector to improve health sector readiness to address PE in the context of health, and were used to develop the Healthy Work Collaborative, a cross-sectoral health promotion capacity building policy, systems, and environmenta change initiative to address PE.